Urban Environment and Health Consciousness: A Comparative Study of Physical Activity, Lifestyle, and Obesity Among Reproductive Age Women in Amman and Budapest (Baltic Journal of Sport and Health Sciences, 2026)
This comparative cross-sectional study examines the relationships between urban environmental factors, physical activity (PA), and obesity among reproductive-age women (18–45 years) in Amman, Jordan (n = 399) and Budapest, Hungary (n = 401). Using a bilingual (Arabic/Hungarian–English) survey, we assessed PA levels (vigorous, moderate, walking), built/social environmental influences, and BMI. Key findings revealed that Hungarian women had significantly higher PA levels (t(798) = 7.97, p < .001, d = 0.56) and lower obesity rates (t(693.61) = –10.32, p < .001, d = 0.73) than Jordanians. Built environment features (sidewalks, recreational access) positively predicted PA (β = 0.203 and 0.158, respectively; p ≤ .001), while social factors (crime, traffic) showed no significant effects. Mediation analysis confirmed PA partially mediated the environment–BMI relationship (indirect effect: b = –0.101, 95% confidence interval (CI) = –0.218, –0.009). Correlations between PA domains and BMI were strongest for vigorous (r = –0.178) and moderate PA (r = –0.177). Despite non-significant city–environment interactions (p = .544), results underscore how urban design disparities contribute to health inequalities among adult females. These findings highlight the need for context-specific interventions to enhance activity-supportive environments, particularly in cities with limited infrastructure.